DEVELOPMENT OF OPTIMAL EXPERIMENTAL THERAPEUTIC REGIMENS ADMINISTRATION OF IMMOBILIZED INTERFERON α-2b - O. G. Shitikova; E. Yu. Sherstoboev; N. V. Masnaya; M. G. Danilets; E. S. Trofimova; A. A. Ligacheva; P. G. Madonov; D. N. Kinsht; K. I. Ershov; M. A. Shilova (Бюллетень сибирской медицины)
The development of optimal experimental therapeutic schemes of immobilized interferon α-2b (production of JSC «Siberian Center for Pharmacology and Biotechnology», Novosibirsk) administration was conducted in the frame of the common program of pre-clinical study. The drug being studied was administered intragastrically for 3, 5 and 7 days in the therapeutic dose (1.8 × 105 IU/kg).  Experimental evaluation of immunotropic properties of immobilized interferon α-2b was carried out at in vivoexperiments in outbred CD1 male mice with using of following tests: the study of drug effect on the phagocytic activity of peritoneal leukocytes (the relative number of phagocytes and the number of bacteria which were assimilated by phagocytes were assessed); the study of drug effect on the humoral immune response (the total number of splenocytes, the relative and absolute number of antibody-forming cells and their functional activity were determined); estimation of drug effect on the cellular immune response with the using of delayed-type hypersensitivity test induced by sheep red blood cells. Based on these data we concluded that course administration of immobilized interferon α-2b in the therapeutic dose for 5 days increased phagocytosis of neutrophils and humoral immune response most effectively. Cell-mediated immune response was significantly increased after 7-fold administration of studied drug.